Humanise : why human-centred leadership is the key to the 21st century - Howard, Anthony (John Wiley & Sons Australia, 2015)
Legendary leaders change the world by putting leadership at theservice of humanity Humanise is a comprehensive look at human-centredleadership, providing insight and guidance for those who want tochange the world. A deep examination of the concept of moralleadership, this book examines what it is, how it's acquired, andhow it can be applied in business, government, and society. Readerswill gain insight into predominant leadership styles exemplified ingovernments and organizations around the world, and discover themissing pieces that come together to more effectively guide peoplethrough challenges and transitions. With a focus on building asolid foundation, a strong moral compass, and deep empathy forothers, this book shows you how to be a leader wherever you are, build your leadership capability, and make a positive impact on theworld. We are facing a crisis of leadership. Where are the newMandelas' What type of person is that' What are their qualities andattributes' Who will lead us into the future' Humanise is abook for people who want to be the very best version of themselves, the best leader they can be, and impact the world for good.-Discover a different perspective on the leadership crisisthroughout the world -Create your own leadership foundation starting with yourpurpose and principles -Turn your personal moral values into a leadership style thatwill benefit and inspire others -Influence the individuals and world around you to become a partof the solution Following in the footsteps of Mandela and Ghandi, this bookexplains why great leadership is human-centred, and how you canbecome such a leader, no matter who you are or what position youare in. For those interested in picking up the torch and guidingthe way, Humanise provides a roadmap to the version of youyou've always wanted to be, and that the world needs you to be.